Análise de fatores de risco para osteonecrose dos maxilares induzida por ácido zoledrônico: um estudo observacional retrospectivo - Carlos, Anna Clara Aragão Matos (2023)
Introduction: Drug-induced osteonecrosis of the jaws (MMO) is defined as bone exposure in the maxillomandibular region for more than eight weeks in patients with no history of radiotherapy and with a history of medication use, such as zoledronic acid. Drugs that depress bone metabolism. Objetive: To evaluate the risk factors for MMO in patients with solid tumors undergoing treatment with zoledronic acid. Materials and methods: A retrospective cohort study, in which the medical records of patients at the Hospital Haroldo Juaçaba/Instituto do Câncer do Ceará (HHJ/ICC) treated between the period 2012-2019 were evaluated using the Toxicity Scales tool available in the system. Tasy electronic medical record. The CTCAE scores (1-5) for OMM that the multidisciplinary team assigns to all patients in each chemotherapy cycle were collected and the medical records were retrieved to assess risk factors (tumor type and phenotype, age, sex, concomitant use of hormone therapy). Data were expressed as absolute and percentage frequencies of each degree of MMO, which were associated with other variable using fisher´s exact test or pearson´s chi-square test and multinominal logistic regression. Subsequently, Kaplan-meier curves were constructed to determine the overall survival of patients with and without OMM, which were compared using the log-rank mantel-cox test (SPSS 20.0, p<0,05). Results: It can be see that the prevalence of MMO in patients undergoing treatment for breast and prostate cancer as 6,47%, aged <50 years (p = 0,009), cytotoxic chemotherapy sush as Methotrexate (p = 0,023), Paclitaxel (p = 0,005), Capecitabine (p < 0,001), Gemcitabine (p = 0,007) and Bicalutamide (p = 0,016), amount of ZA infusions (p < 0,001) and hormone therapy (p = 0,007), in addition, a slight reduction was observed survival and increased use of antidepressants (p = 0,014). Conclusion: The prevalence of OMM in the studied sample was 6,4%, and the concomitant use of chemotherapy, hormone therapy and antidepressants are significant risk factors for the devolopment of this condition. Therefore, it is necessary to increase attention to these patients to prevent this condition from compromising the prognosis of these individuals.